strategi perencanaan investasi pada saham syariah di era pandemi covid-19 - Chamidi, Achmad Luthfi (UIN Sayyid Ali Rahmatullah, 2021)
Entering the digital age makes national boundaries biased, Where there is no longer an obstacle for all nations in the world to one another Communicating and transacting business are only minutes at that distance Very far though. Let alone the development of the Indonesian economy The year 2020 is full of fluctuations with covid-19 viruses yet Indonesia can look out for. The stock market with an islamic investment instrument It is an activity in the capital market that does not conflict with sharia principles. Sharia's own principle in the capital market is based on the decrees of the qur 'an and hadits That governs worship and human activities in your business (fiqh). stock Sharia is a valuable document presenting the inclusion of capital into At the stock exchange. The purpose of this research is; for Provides insight into prospective investors affected by covid - 19 in taking a decision to invest. This kind of research is Qualitative with a literature study approach with a data source that is secondary data That were generated from previous research, and other reference sources There are things that prospective investors need to know. especially Investors from socially affected covid-19 are involved With the planning and management of investments on sharia stock. It is Demands that investors know boundaries and rules.